Use of webQDA software on qualitative nursing research: an experience report - Ana Larissa Gomes Machado; Neiva Francenely Cunha Vieira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to report the user experience of the webQDA software in the support of qualitative data analysis about health literacy of older adults. Methods: quasi-experimental research developed from January 2014 to January 2015, with 118 older adults, all of whom were interviewed to assess the level of health literacy. Interviews were carried out before and after four educational interventions, according to Freire's method named Culture Circle. The interviews were transcribed and entered in the software, which highlighted the analytical categories. Results: the systems of sources, interpretative encoding and questioning of the data available in the software allowed the construction of three categories for the literacy levels and four categories for their dimensions. Final considerations: We concluded that the webQDA software enables the structured encoding of qualitative materials, ensuring faster and effective management of data with systematization and analytical transparency.